D-enantiomeric antibiofilm peptides effective against anaerobic Cutibacterium acnes biofilm - Jennifer Varin-Simon; Evan F. Haney; Marius Colin; Frédéric Velard; Sophie C. Gangloff; Robert E. W. Hancock; Fany Reffuveille (Microbiology Spectrum)
ABSTRACT The emergence of antibiotic resistance, biofilm formation, and internalization by host cells contribute to a high risk of chronic infections, highlighting the necessity to develop novel therapeutic strategies. Identification of natural host defense peptides (HDPs) with promising antimicrobial and antibiofilm activities led to the development of synthetic peptides with broad-spectrum efficacy. However, few studies have examined their effect on anaerobic bacterial species. This study aimed to test the effect of synthetic HDPs on Cutibacterium acnes, an anaerobe species involved in 10% of prosthesis joint infections (PJI). A preliminary screen identified three peptides (DJK5, AB009-D, and AB101-D) with promising activity against four C. acnes strains (two of which were isolated from PJI). A bactericidal effect was observed for the three peptides with 50% of planktonic bacteria killing for AB009-D and AB101-D after only 3 hours of contact. DJK5 and AB009-D inhibited the C. acnes adhesion on plastic and titanium supports with a 2-log decrease in bacterial cells. In the presence of peptides, the morphology of C. acnes cells was altered with an increase in cell length observed, especially for one of the non-PJI-related strains. Against mature biofilms, AB101-D was the most effective with an approximate 2-log decrease in adhered CFUs, indicating the induction of bacterial dispersion or death. DJK5 also inhibited C. acnes internalization by osteoblasts, with a reduction of the internalized bacteria quantity for three strains. Overall, this study demonstrates that synthetic HDPs are effective against anaerobic bacteria and hold promise as novel therapeutic candidates to prevent or treat C. acnes PJIs.IMPORTANCEThe emergence of antibiotic tolerance highlights the necessity to develop novel therapeutic strategies with promising antimicrobial but also antibiofilm activities. In this study, we tested the effect of synthetic host defense peptides (HDPs) on Cutibacterium acnes, an anaerobic species, rarely studied, whereas involved in 10% of prosthesis joint infections (PJI). In our study, we demonstrate that the selected synthetic HDPs are effective against this anaerobic bacteria, both as a preventive treatment (effect on planktonic growth, bacterial adhesion, and biofilm formation) and against internalization of C. acnes by osteoblasts, revealing that these peptides are promising as novel therapeutic candidates to prevent or treat C. acnes PJIs.